Systems Biology : Applications in Cancer-Related Research - Juan, Hsueh-Fen; Huang, Hsuan-Cheng (World Scientific, 2012)
This volume presents an overview of recent developments in systems biology and their applications in cancer-related research. The ongoing advances in our understanding of genomics and proteomics, coupled with the development of new and more robust tools, have led to an emphasis on analyzing biological systems at multiple levels. Thus, there is a need to integrate different types of data into a comprehensive "systems" view. Written by active researchers in the emerging areas, this book gives senior undergraduate students, graduate students and new researchers an idea of where the frontiers of s.